2018
DOI: 10.3324/haematol.2018.209015
|View full text |Cite|
|
Sign up to set email alerts
|

Association of early disease progression and very poor survival in the GALLIUM study in follicular lymphoma: benefit of obinutuzumab in reducing the rate of early progression

Abstract: We evaluated early disease progression and its impact on overall survival (OS) in previously untreated follicular lymphoma patients in GALLIUM ( clinicaltrials.gov identifier: 01332968 ), and investigated the effect on early disease progression of the two randomization arms: obinutuzumab-based versus rituximab-based immunochemotherapy. Cause-specific Cox regression was used to estimate the effect of treatment on the risk of disease progression or dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 16 publications
4
62
1
4
Order By: Relevance
“… 28 Whether the recently described progression of disease within 24 months of initiating treatment end point is a more reliable surrogate of OS in patients with FL receiving 1L immunochemotherapy with or without maintenance remains to be established. 29 - 32 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Whether the recently described progression of disease within 24 months of initiating treatment end point is a more reliable surrogate of OS in patients with FL receiving 1L immunochemotherapy with or without maintenance remains to be established. 29 - 32 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with progression of disease within 24 months of completing induction chemoimmunotherapy (POD24), which made up 19% of patients in this data set, had poorer outcomes compared with those with longer remission durations (5‐year overall survival [OS]: 50% vs. 90%, respectively) even after adjustment for Follicular Lymphoma International Prognostic Index (FLIPI) score (discussed below) . These results were validated in the University of Iowa and Mayo Clinic Molecular Epidemiology Resource data sets , and in the GALLIUM study and using the FLASH data set . Additionally, a longer duration from diagnosis to progression (i.e., event‐free survival of >12 months after diagnosis) did not result in excess mortality compared with the age‐ and sex‐matched general population .…”
Section: Risk Stratificationmentioning
confidence: 68%
“…Effect of maintenance on POD24 events remains poorly studied. Gallium trial comparing rituximab or obinutuzumab in induction and in subsequent maintenance showed fewer early disease progression events occurred in obinutuzumab versus rituximab immunochemotherapy patients, with an average risk reduction of 46.0% and cumulative incidence rate 10.1% versus 17.4% [26]. However, it is unclear, whether POD24 reduction was caused by higher efficacy of particular obinutuzumab-based induction or due to perhaps more potent obinutuzumab maintenance.…”
Section: Discussionmentioning
confidence: 99%